2020
DOI: 10.23960/ijebe.v3i1.73
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking The Secret of E-Loyalty: A Study from Tiktok Users in China

Abstract: TikTok is a recent global phenomenon and in the first quarter of 2020 alone it has TikTok been downloaded 315 million times. People love it because it allows them to spur creativity in video content and increase their online presence. Founded by a Chinese company, this social networking application has become a trend for about 400 million loyal users in China. However, studies about how people become loyal to TikTok are lacking. This study aims to examine the effect of service quality and satisfaction to loyal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Bitner (1990) revealed that satisfaction significantly influences loyalty through structural equation models. Susilo (2020) found that e-satisfaction has a positive impact on e-loyalty. These results show that customer satisfaction can increase customer loyalty.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
“…Bitner (1990) revealed that satisfaction significantly influences loyalty through structural equation models. Susilo (2020) found that e-satisfaction has a positive impact on e-loyalty. These results show that customer satisfaction can increase customer loyalty.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
“…Meanwhile, e-Satisfaction can be measured by seeing how far the disparity is betwixt client desires and what they encounter when using the cater ( Gopi & Samat, 2020) . Creating e-Satisfaction can produce a number of advantages, including client loyalty to specific outcomes and personal references that contribute to business success Ramli, 2019b;Susilo, 2020). E-Satisfaction is a flavor as a form of assessing the spectacle of a outcome or cater based on client hopefulness after forming a buying at a corporation with electronic aid ( Purfancyo, 2022) .…”
Section: E-satisfactionmentioning
confidence: 99%
“…Pada penelitian Muharam et. al., (2021), dan Susilo (2020) software yang digunakan untuk mengolah data adalah SEM PLS sedangkan pada penelitian ini menggunakan software AMOS. Pada penelitian Sarigih (2019), dan Permada dan Yasa (2018) objek yang digunakan adalah aplikasi shopee sedangkan pada penelitian ini objek yang digunakan adalah TikTok Shop.…”
Section: Pendahuluanunclassified
“…Penelitian sebelumnya yang meneliti mengenai hubungan pengaruh e-service quality Terhadap e-satisfaction, yaitu Muharam et al, (2021), Kurniati et al, (2020), Susilo (2020), Khan et al, (2019), Ghane et. al., (2011), Ting et.…”
Section: Pengaruh E-service Quality Terhadap E-satisfactionunclassified